2015
DOI: 10.1253/circj.cj-15-0064
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Dysfunction

Abstract: Despite the growing number of patients affected, the understanding of diastolic dysfunction and heart failure with preserved ejection fraction (HFpEF) is still poor. Clinical trials, largely based on successful treatments for systolic heart failure, have been disappointing, suggesting that HFpEF has a different pathology to that of systolic dysfunction. In this review, general concepts, epidemiology, diagnosis, and treatment of diastolic dysfunction are summarized, with an emphasis on new experiments suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
83
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 65 publications
8
83
0
1
Order By: Relevance
“…Increased oxidative stress and cardiac oxidation has also been associated with diastolic dysfunction[47]. The toxic effects of ROS can be prevented in part by the antioxidant enzyme system including GSH-Px, SOD and catalase[55].…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative stress and cardiac oxidation has also been associated with diastolic dysfunction[47]. The toxic effects of ROS can be prevented in part by the antioxidant enzyme system including GSH-Px, SOD and catalase[55].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 2 decades, the syndrome of heart failure with preserved ejection fraction (HFpEF) received a lot of attention 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19. However, little therapeutic progress was made 20, 21, 22, 23, 24, 25, 26, 27.…”
Section: Introductionmentioning
confidence: 99%
“…As a whole, HFpEF has been extensively reviewed 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19. The present review focuses on 4 commonly encountered clinical phenotypes of HFpEF and their comorbid conditions (Figure).…”
Section: Introductionmentioning
confidence: 99%
“…The isovolumic relaxation time constant (τ) is used to characterize the active phase of cardiac relaxation using the exponential intra-ventricular pressure decline during early diastole. This value is measured clinically using indirect methods that correlate with the pressure derived relaxation time constant [9]. This index has been shown to be inversely related to diastolic cardiac function and represents the active energy consumption portion of ventricular relaxation [10].…”
Section: Introductionmentioning
confidence: 99%
“…This index has been shown to be inversely related to diastolic cardiac function and represents the active energy consumption portion of ventricular relaxation [10]. It has been shown that this index is useful in the diagnosis or theraputic follow-up of patients with diastolic heart failure or Heart Failure with preserved Ejection Fraction (HFpEF) [9], [11] . The systolic/diastolic stiffness ratio is another potential functional index that provides a ratio-metric measure of the contractile and compliance states of the myocardium.…”
Section: Introductionmentioning
confidence: 99%